KEMAMPUAN LITERASI SAINS SISWA PADA MATERI PERUBAHAN LINGKUNGAN DI SMAN 1 PASIR PENYU - Dita Aldeasari Nurrizki; Yuslim Fauziah; Darmawati Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The challenges of 21st century learning require the learning process to be more active. Conventional learning methods are still widely used in various learning so that student interaction in learning is still very low. One of the abilities that students must have in this 21st century learning is scientific literacy skills, namely the ability of students to use scientific knowledge, identify problems and draw conclusions based on scientific evidence in making decisions. The results of the PISA study show that the scientific literacy of Indonesian students is in the "low" category. The low scientific literacy of students is caused by several factors in the education system, such as teachers, students and the family environment. This study aims to determine students' scientific literacy skills and the factors that cause students' scientific literacy skills on the material of environmental change. This research was conducted at SMAN 1 Pasir Penyu in the semester of the 2020/2021 academic years. The research method used is descriptive quantitative with research instruments in the form of tests and questionnaires with research subjects 58 students of SMAN 1 Pasir Penyu. The results of this study indicate that students' scientific literacy skills are in the low category (59,82%). This can be seen from the knowledge aspect (62,64%), context aspect (59,95%), and competence aspect (69,01%). Factors that cause the low scientific literacy skills of students on the material of environmental change are self-factor with a percentage of 66,66%, namely interest in learning, learning motivation, study habits, and students' understanding of the material, family environmental factors with a percentage of 69,82%, namely the lack of parental guidance, and school environment factors with a percentage of 71,60%, namely the way teachers teach.Key Words: Science Literacy, Material of Environmental Change